Babbel Language Learning Podcasts - Sporn, Zachary; Chanter, Julia; Meehan, Daniel (International Journal of Advanced Corporate Learning (iJAC), 2020)
Winner of the 2020 IELA E-Learning Award in the category Mobile Learning, Babbel’s slate of language learning podcasts provide innovative audio learning experiences, designed and hosted by linguistic experts. This article describes the pedagogical method and expertise behind Babbel’s podcasts along with some best practices for creating effective audio-based learning experiences.